Membuat Trainer Kit Suzuki Smash Titan "Sistem Penerangan" - SALEH, Abdul Rachman ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Automotive engineering is a branch of mechanical engineering science that studies how to devise, how to make, and how to develop road-transportation tools that use machines, especially motorcycles, cars, buses, and trucks. Automotive engineering integrates elements of mechanical, electrical, electronical, secure, environmental, and also mathematical, physical, chemical, biological, and managerial sciences. The objective of the making of the Suzuki Smash Titan trainer kit is to help students to learn motorcycle electricity. In making the trainer kit, some methods are used to collect the data: literature and direct observation methods. The result of the test shows that the trainer kit can operate well. The writer expects that the trainer kit can motivate other students to make other useful trainer kits.